Hubungan antara Kebisingan terhadap Prestasi Belajar Siswa Kelas VII Jakarta - Dhelfina Athalia; Viginia Virginia; Sintya Sukmawati (Humanitas (Jurnal Psikologi), 2018)
Noise can caused problem in urban education, especially school which near the source of noises. Noises means every sound that can attract attention, disturbing, or dangerous for daily routine, noise in general defined as sound that is not desired and also caused environment polution. Noise can come from various place, such as: highway, train station, airport, etc. Learning achievement is an evidence of successful learning or ability in student in doing learning activities based on the weight they have achieved. This research using a correlational pearson method, that is for looking for relationship between noise and learning achievement. We do this research in X Public Junior High School in Jakarta in 17 boys student and 18 girls student with aged between 12-14 years old with quetionnaire. The reability test result in two section in “quetionnaire about class noises” showed that this quetionnaire is measured what is supposed to be measured (reliable) because the result of reability test is >0,60. After being tested the correlation between noise and students learning achievement, it can be stated that there is no correlation between noises with students learning achievement of Junior High School X Jakarta